25 TAVI operator radiation dose compared to PCI and ICD operators: do we need additional radiation protection for trans-catheter structural heart interventions. (9th June 2011) - Drury-Smith, M; Maher, A; Douglas-Hill, C; Singh, R; Bhabra, M; Cotton, J; Khogali, S
Abstract : Introduction: Trans-catheter cardiac aortic valve implantation (TAVI), implantable cardiac defibrillators (ICD), and percutaneous coronary intervention (PCI), are common procedures associated with radiation exposure to the operator and the patient. Radiation dose exposure is cumulative and if above the recommended annual levels may have significant consequences for the operator. The radiation dose TAVI operators are exposed to is not widely known, but it is an important consideration in view of the increasing volume of procedures and the potential risks of over-exposure. Our aim was to monitor and compare, radiation exposure time, dose, and individual operator dose, in TAVI, PCI and ICD. Method: Ten TAVIs were performed, 6 via the trans-femoral route and 4 via the subclavian approach. Radiation protection was employed in all cases using standard lead skirts and screens. During each procedure the radiation dose exposure was monitored for each operator using ThermoLuscent Dosemeters (TLD) on the left finger (LF), right finger (RF) and forehead. The six TAVI procedures performed via the transfemoral approach used only two operators, while the subclavian approach involved three operators. The third operator was a surgeon who was nearest to the x-ray images. Radiation exposure doses were also collected from ICD and PCI operators during the same period, using the same type of TLDs on LF and RF. Operator specific radiation doses were obtained from a central RRPPS Approved Dosimetry Service. PCI was considered a standard trans-catheter procedure. TAVI and ICD operator doses were compared to the mean standardised PCI operator dose. Results: The mean exposure times and doses for the different types of trans-catheter procedures performed are detailed in the tables below. Despite the use of standard radiation protection measures, the mean dose to operators undertaking TAVI was 6 times higher than the trans-femoral PCI operator (p=0.008). The mean radiation exposure time of TAVI was seven times more than PCI. Although subclavian TAVI and ICD procedures were expected to be comparable with respect to operator dose, subclavian TAVI operators have an unexpectedly higher dose (p=0.03). Conclusions: Overall TAVI operators are exposed to significantly higher radiation doses compared to PCI and ICD operators. Additional radiation protection for TAVI operators is strongly advocated. We are currently evaluating the impact of using a RADPAD as additional protection during TAVI procedures.